183 A Systematic Review of Sample Size Calculations in High-Profile Surgical Trials That Use Patient-Reported Outcome Measures. (28th February 2022) - Jacklin, C.; Rodrigues, J.; Collins, J.; Cook, J.; Harrison, C.
Abstract: Background: Patient reported outcome measures (PROMs) are increasingly recognised as a measure of treatment efficacy in randomised controlled trials (RCTs). It can be difficult to determine meaningful target differences in PROM scores for sample size calculations and this can risk over-recruitment and/or erroneous trial conclusions. The Difference ELicitation in TriAls (DELTA 2 ) statement sets recommendations for sample size calculations in RCTs including target difference determination. We aimed to evaluate sample size calculations from high-profile surgical RCTs that used PROMs as their primary outcome, against DELTA 2 standards, with a focus on target differences. Method: Pubmed was systematically searched for surgical RCTs published in the five highest ranking journals, by Thomson Reuters impact factor, for medicine and surgery. Studies were included if surgery was the intervention and/or comparator arm, and a PROM was the primary outcome. Surgery was defined as using instrumentation to change macro-anatomy with the aim of improving health. Data were extracted with a piloted data collection sheet that included the DELTA 2 reporting recommendations. Results: Most target differences used in sample size calculations were determined with suboptimal techniques and target difference justification was overall poor. In this sample, £28 million of UK public research spending supported trials with poor target difference justification. Conclusions: In this sample of trials, sample size calculations were generally not reported to DELTA 2 standards. There was frequent use of sub-optimal methods to determine the target difference. This risks over-recruitment and/or erroneous trial conclusions. Clinicians should be aware of these potential pitfalls when interpreting published trials.